Kay tagal na pala ng noon - Sison, Julienne Kristine Alvis 1989-; Campos, Patrick F.; University of the Philippines. College of Mass Communication (2014)
"Kay Tagal Na Pala Ng Noon is a film about Nica, a young nurse torn between career advancement in Australia or fidelity to a loved one. Meanwhile, the film's supporting character, Lola, spends her days in a home for the aged, suffering from Alzheimer's disease. As the narrative progresses, the relationship between the two characters is revealed. The use of Melodrama as framework highlights the main character's struggles with the social pressure outside and her struggles within. The film also attempts to explore Nica's "mind" as a projection of her thoughts presented through the film's non-linear story-telling."
Vita.
Thesis (A.B. Film)--University of the Philippines Diliman
Keywords: Social pressure; Family relationships; Melodrama